(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Issues of Modernity in Indian Philosophy has confronted as far back as the appearance of Modernity in Indian subcontinent. It is outstanding that amid the most recent three centuries, European nearness, both political and cultural, in India has been exceptionally wide spread. The Europeans whose political appearance on the Indian scene turned out to be very noticeable just towards the finish of the eighteenth century, at that point they had presented English education in India. The presentation of the elites of the nation to it to a great extent represent the decay of the traditional method for philosophizing, which was some way or another went on undisturbed for quite a long time disregarding long Muslim rule in the nation. The damage was devastating to the point that even now we discover Indian philosophers meandering around erratically in the philosophical field, not certain what to do and how to do. Step by step Indian savvy people and later scholastics too started utilizing an ever increasing number of European ideas and classes to the degree that Indian philosophizing was shaken at its establishment. So, in this Research Paper, we overviewd Modernity in Western and Indian perspective and the Problem of Modernity in India in detail.